Wireless power transmission using a resonant coil consisting of conductive yarn for wearable devices. Issue 14 (September 2016) - Jeong, Min Joo; Yun, Tae-il; Baek, Jong Jin; Kim, Youn Tae
This paper presents a wireless power transmission method that uses magnetic resonant coupling with resonant coils made of conductive yarn that can be integrated into clothing. The conductive yarn consisted of silver-plated copper and polyester filaments. The transmission characteristics of the yarn and copper resonant coils were compared using simulation and measurement tools. It was determined that the signal loss of the conductive yarn resonant coils was higher than that of the copper coils. However, the increase in the signal loss variation was less than 1 dB when the transmission distance was less than 6.5 cm. The conductive yarn resonant coils were placed in the shoes and trouser cuffs of a human subject, and the transmission efficiency was measured after the received alternating current power was converted to direct current power using an alternating current–direct current converter. The measurement results showed a maximum transmission efficiency of 50%; the average transmission efficiency was 45%, despite the change in the coil shape and alignment conditions due to body movement. In addition, the results demonstrated an excellent transmission efficiency of over 40% when the subject was moving at a speed of 6 km/h. It was also shown that the textile coils can be an integrative solution, overcoming clothing comfort and continuous power supply for a new generation of wearable devices.